2015
DOI: 10.1111/joa.12371
|View full text |Cite
|
Sign up to set email alerts
|

The role of fasciae in Civinini–Morton's syndrome

Abstract: This study evaluates the pathogenetic role of the perineural connective tissue and foot fasciae in Civinini-Morton's neuroma. Eleven feet (seven male, four female; mean age: 70.9 years) were dissected to analyse the anatomy of inter-metatarsal space, particularly the dorsal and plantar fasciae and metatarsal transverse ligament (DMTL). The macrosections were prepared for microscopic analysis. Ten Civinini-Morton neuromas obtained from surgery were also analysed. Magnetic resonance images (MRIs) from 40 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
2
22
0
3
Order By: Relevance
“…A similar organization was found by Reina & Sala-Blanch (2015) in an anatomic study of the sciatic nerve. This microscopic organization corroborates the hypothesis of Macchi et al (2007) and Stecco et al (2015) regarding the musculo-cutaneous nerve, which proposed a telescopic model for nerve sliding. The nerve with its connective components is organized in concentric layers which act as gliding interfaces between each other and between the nerve and adjacent tissues.…”
Section: Discussionsupporting
confidence: 90%
“…A similar organization was found by Reina & Sala-Blanch (2015) in an anatomic study of the sciatic nerve. This microscopic organization corroborates the hypothesis of Macchi et al (2007) and Stecco et al (2015) regarding the musculo-cutaneous nerve, which proposed a telescopic model for nerve sliding. The nerve with its connective components is organized in concentric layers which act as gliding interfaces between each other and between the nerve and adjacent tissues.…”
Section: Discussionsupporting
confidence: 90%
“…reported that, in 59% of cases, the sartorius muscle had a medial aponeurotic expansion from its tendinous origin to the ASIS, which ensheathes the LFCN, and attached to the inferior border of the inguinal ligament . Minimal dissection referring to the sartorius muscle would be helpful for preventing excessive injury to the connective tissue surrounding the LFCN with scar tissue formation, which may impair normal sensation and the mobility of the thigh …”
Section: Discussionmentioning
confidence: 99%
“…5 Minimal dissection referring to the sartorius muscle would be helpful for preventing excessive injury to the connective tissue surrounding the LFCN with scar tissue formation, which may impair normal sensation and the mobility of the thigh. 23,24 The symptoms of MP are known to be aggravated by prolonged standing or repetitive hip extension, and relieved by sitting. 2,9 In a few of the specimens in this study the LFCN directly entered the fascia of the tensor fascia lata muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Эта патология чаще возникает на фоне плоскостопия и ПФ, как последствие травм плюсны («маршевый перелом»), а также при ношении узкой обуви на высоком каблуке, значительно нарушающей биомеханику свода стопы. Синдром Мортона проявляется жжением, покалыванием и парестезиями в области пальцев стопы, чаще среднего и безымянного, возникающими или усиливающимися при ходьбе и значительно уменьшающимися в состоянии покоя [36,42].…”
Section: стопаunclassified
“…В ряде случаев полезную информацию дает рентгенография, при которой определяются в первую очередь кальциноз мягких тканей как косвенный признак энтезопатии таза, а также «пяточная шпора» при ПФ [35,37]. Для точной диагностики туннельных синдромов может потребоваться и проведение электромиографии [36,41,42].…”
Section: стопаunclassified